PENGEMBANGAN BAHAN AJAR MENGGUNAKAN EXPANDING COMMUNITY APPROACH, PEMBENTUKAN KONSEP, DAN SPIRAL APPROACH PADA MATERI PPKn SD/MIx - Maha Lastasa Buju Basafpipana Habaridota (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
This research is the developing of teaching materials that aim to carry out the development of Grade 1 Elementary PPKn Teaching materials on the material "I Love Pancasila" by expanding the community approach, concept formation and spiral approach based on independent learning curriculum. The expanding community approach is used to detail relevant examples starting from oneself, the family environment, the school environment and the community. Concept formation is intended to draw a definition according to its conception, and the spiral approach is intended to create LKPD by integrating the values that exist in the essence of PPKn it self, namely Pancasila and nationality. The development was carried out by involving PGMI university students in 3rd semester academic year 2022/2023. The research methodology used research and development (R & D) development with a 4-D model (Define, Design, Develop and Disseminate), but specifically research only reached the Develop stage. The research results based on the distribution of instruments for each judges obtained the development of teaching materials by expanding community approach, concept formation and spiral approach from material experts with an average of 85% in the very feasible category, design experts by 89% in the very feasible category, and language expert by 85% with very feasible category. Based on the data obtained, it can be concluded that PPKn teaching materials for 1st grade SD/MI using an expanding community approach, concept formation and a spiral approach are very feasible to use.